Updates in diagnosis and management of paediatric mastocytosis. Issue 2 (2nd April 2023) - Tiano, Rasa; Krase, Ifat Z.; Sacco, Keith
Abstract : Purpose of review: Paediatric mastocytosis is a rare clonal disorder characterized by the overproduction and organ infiltration of mast cells. Symptoms are due to mast cell mediator release. Cutaneous mastocytosis is the most common presentation in children with systemic disease being rare. Our aim is to provide a practical guideline in differentiating subtypes of paediatric mastocytosis while providing actionable recommendations on diagnosis, clinical management, follow-up and prognosis. Recent findings: Longitudinal cohort studies of paediatric cutaneous mastocytosis have shown spontaneous remission with favourable prognosis. Hereditary alpha-tryptasemia may coexist with mastocytosis; thus, screening for this disorder is recommended. There is an emerging role for serum tryptase in asthma endotyping and potential for using therapeutic tryptase inhibitors. Summary: Morbidity in paediatric mastocytosis typically arises from symptoms secondary to mast cell mediator release. Prognosis for nonaggressive disease is typically favourable; however, risks for anaphylaxis and psychosocial morbidity may be underestimated. Symptomatic management and anticipatory guidance may help support patients and families throughout the disease course.